2008
DOI: 10.1186/1743-422x-5-14
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp120 N-linked glycosylation differs between plasma and leukocyte compartments

Abstract: Background: N-linked glycosylation is a major mechanism for minimizing virus neutralizing antibody response and is present on the Human Immunodeficiency Virus (HIV) envelope glycoprotein. Although it is known that glycosylation changes can dramatically influence virus recognition by the host antibody, the actual contribution of compartmental differences in N-linked glycosylation patterns remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
(43 reference statements)
2
10
0
4
Order By: Relevance
“…HIV-1, in particular, is reported to acquire distinct envelope glycosylation patterns of the producer cell (49), potently modulating the infectivity of progeny virions (50). Therefore, we evaluated whether the production of HIV-1 by different host cells affects the transcytosis efficiency of the virus through epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1, in particular, is reported to acquire distinct envelope glycosylation patterns of the producer cell (49), potently modulating the infectivity of progeny virions (50). Therefore, we evaluated whether the production of HIV-1 by different host cells affects the transcytosis efficiency of the virus through epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-free HIV-1, along with cell-associated virus, is present in breast milk (9, 49) and semen (1, 24, 26) and thus available for transcytosis across recipient small intestinal and rectal columnar epithelium during vertical and homosexual transmission, respectively. Presumably, transcytosis through HT-29 model epithelium is initiated by viral envelope binding to the epithelial surface.…”
Section: Discussionmentioning
confidence: 99%
“…29 In this study, Ho and co-workers analyzed a gp120 region spanning C2-V5 by aligning env protein sequences from 305 clones derived from plasma and other compartments in 15 individuals infected with HIV-1. 29 In the paper by Ho and collaborators there is no reference to the pattern of sequons in V4, supposedly due to the high degree of sequence variation and length polymorphism in this region. This may explain the apparent discordance in our data about compartmentalization.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ho et al on the frequency of N-linked glycosylation observed between 15 independent patients, the authors reported that the number of glycosylation sites was not consistent across the different compartments [10]. Plasma compartment viruses have a higher probability for glycosylation at the N-terminal of V4 and within C4 as compared with cellular compartment viruses (e.g., CD4 + T lymphocytes, CD8 + T lymphocytes, monocytes and PBMCs).…”
Section: Glycosylation Adaptation During Compartmentalizationmentioning
confidence: 96%
“…In addition, the specific presence of the glycosylation site in the C3 region can enhance virus fusogenicity and faster entry kinetics in CCR5 viruses [9]. Beyond the effect of glycosylation on receptor binding, glycans on gp120 can potentially influence the virus's ability to infect different cellular compartments during active infection [10], which assists the virus in evading the host immune system [11] and influences the efficiency of host-host transmission events [12]. In this review, we will mainly be focusing on the glycosylation of gp120 in order to determine its influence on HIV-1 compartmentalization, disease progression, viral evolution and gp120 structure modulation.…”
Section: Hiv-1 Envelope Glycoprotein and Its Glycosylationmentioning
confidence: 98%